Machinability Performance Of Titanium Alloy When Using Modified RBD Palm Oil Dielectric Fluid In Electrical Discharge Machining Process - Ishak, Muhammad Shazwan; Ahmad, Said (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Electric discharge machining (EDM) is a non-traditional machining because it does not use hard tools or abrasive materials, otherwise it uses EDM to cut materials that are difficult to machine. Titanium has a low Young’s modulus and high hardness value, making it difficult to process. It is one of the materials used in EDM. In this project, based on the selection of appropriate parameters, the machinability performance of titanium alloy and copper electrode when modified RBD palm oil dielectric fluid is used in EDM is analyzed. Peak current (Iₚ), voltage (V), pulse on time (tₒₙ) and pulse off time (tₒff) are the parameters selected in this project. In this experiment, a copper electrode with a diameter of 10 mm is used to cut a titanium alloy. Palm oil properties was modified through transesterification process to imitate properties of conventional hydrocarbon dielectric fluid which is kerosene. The modified RBD palm oil is then being used in the EDM process to machine titanium alloy and the machinability were observed. From the reviewed, the data collected show that MRR of titanium alloy when using modified vegetable oil is higher than when using kerosene. EWR also show that there is decreasing in value when using modified vegetable oil, while for surface roughness, kerosene displayed higher surface roughness in the surface of working piece. To sum it up, by utilizing modified vegetable oil in the electrical discharge machining process as a dielectric fluid, the machining process will become sustainable and environmental friendly.